Ystruder: Open source multifunction extruder with sensing and monitoring capabilities. (October 2019) - Klar, Ville; Pearce, Joshua M.; Kärki, Pyry; Kuosmanen, Petri
Graphical abstract: Abstract: Syringe pumps are widely used in a multitude of tasks where precise volumes of an extrudate need to be delivered at a specific flow rate. In the past decade various open source syringe pump designs have accelerated scientific research and exploration by reducing costs and introducing new ideas. To further expand the capabilities of open source syringe pumps we introduce a novel syringe pump design, the Ystruder. It features a load cell to monitor the piston force. This capability enables clog detection as well as development of advanced dosing algorithms. The Ystruder can be monitored wirelessly through a browser-based interface that is integrated into the embedded system. The design is modular and simple which facilitates different syringe and motor configurations, to meet a wide range of use cases. Finally, the Ystruder is not limited to functioning solely as a pump as it can be integrated into a wide range of devices such as three-dimensional motion systems. Here the dosing accuracy and repeatability of the Ystruder are quantified, and we demonstrate its functionality both as a syringe pump and a paste extruder for 3D printing.